Graphene Quantum Dots: Controllable Singlet–Triplet Energy Splitting of Graphene Quantum Dots through Oxidation: From Phosphorescence to TADF (Adv. Mater. 31/2020). Issue 31 (4th August 2020) - Park, Minsu; Kim, Hyung Suk; Yoon, Hyewon; Kim, Jin; Lee, Sukki; Yoo, Seunghyup; Jeon, Seokwoo
Abstract : In article number 2000936, Seunghyup Yoo, Seokwoo Jeon, and co‐workers introduce a novel concept for tuning singlet–triplet energy splitting of graphene quantum dots (GQDs) by oxidation control, which induces a dramatic afterglow transition from phosphorescence to thermally activated delayed fluorescence. Matrix‐assisted stabilization of triplet excited states provides ultralong lifetimes to such afterglow emissions at room‐temperature, which enables multilevel information security.